(untitled) (Biological Sciences - PJSIR, 2004)
Citric acid can be produced from various microorganisms such as bacteria, filamentous fungi and yeast by applying various fermentation techniques. Because of its high solubility, palatability and low toxicity, citric acid has now become one of the most commonly used acids. Approximately, 75% of this compound is used as food acidulate and 12% in pharmaceutical industry (Haqet al 2001). Various fungi have been evaluated for citric acid production but best one for abundant citric acid production is Aspergillusniger( Maddox and Brooks 1998). The present study is concerned with the effect of pH and various concentrations of K4Fe (CN)6 and K2HPO 4 on citric acid bio-production and their kinetic analysis